Trensains: The New Pesantren and Shifting Orientation of Islamic Education in Indonesia - Azaki Khoirudin; Abdul Munip; Imam Machali; Hamzah Fansuri (Jurnal Pendidikan Islam, 2022)
Purpose – This study aims to explain the factors of the emergence of “pesantren sains/science pesantren” (Trensains) and their implications for the shift in the orientation of Islamic education in Indonesia. Existing pesantren studies have looked more at practical aspects, such as curriculum development and learning, but not yet at philosophical aspects, which have implications for a shift in the orientation of Islamic education. Design/methods/approach – Data was collected using interviews and documentation. The research, which utilized a phenomenological approach, was conducted at Sragen Muhammadiyah Trensains Senior High School in Central Java and Tebuireng Trensains Senior High School in East Java. The primary respondent was Agus Purwanto, the initiator, founder, and developer of a science boarding school, who had first-hand experience with the events that took place while he was a student at the Pesantren. Findings – The findings of this study suggest that Trensains is a new pesantren genre that was developed as a reaction to the lack of science and technology in the Islamic world due to the heavy jurisprudential emphasis on Islamic education. In the history of the curricula at pesantren, including philosophy as a topic is a novelty. Research implications/limitations – The emergence of Trensains has implications for a shift in the orientation of pesantren in Indonesia from a Sufistic-fiqh orientation to a scientific-philosophical orientation which is marked by the following changes: (1) in the function of transmission and transfer of Islamic knowledge (tafaqquh fī al-dīn) to the study of Islamic sciences general science; (2) from maintaining the Islamic tradition to cultivating the scientific tradition; and (3) from a reproduction of religionists to producers of scientists. However, some drawbacks need to be acknowledged. This study has not discussed Trensains as a whole, and its effectiveness in shaping the character of pesantren is unknown. Therefore, further research is needed to understand the impact and role of Trensains in the development of Islamic education in Indonesia.